2018
DOI: 10.1080/02791072.2018.1508789
|View full text |Cite
|
Sign up to set email alerts
|

The PPARγ Agonist Pioglitazone Fails to Alter the Abuse Potential of Heroin, But Does Reduce Heroin Craving and Anxiety

Abstract: Possibly through its effects on glia, the peroxisome proliferator-activated gamma receptor (PPARγ) agonist pioglitazone (PIO) has been shown to alter the effects of heroin in preclinical models. Until now, these results have not been assessed in humans. Heroin-dependent participants were randomized to either active (45 mg, n = 14) or placebo (0 mg, n = 16) PIO maintenance for the duration of the three-week study. After stabilization on buprenorphine (8 mg), participants began a two-week testing period. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…We previously showed that pioglitazone, a selective PPAR␥ agonist, was highly effective in reducing behavioral responses to stress and preventing stress-induced relapse to alcohol and opioid seeking in rats (Stopponi et al, 2011;Domi et al, 2016;de Guglielmo et al, 2017). Pioglitazone was also shown to reduce heroin craving and anxiety in humans (Jones et al, 2018), and most important, a recent clinical study reported that pioglitazone attenuates measures of nicotine craving (Jones et al, 2017).…”
Section: Significance Statementmentioning
confidence: 99%
“…We previously showed that pioglitazone, a selective PPAR␥ agonist, was highly effective in reducing behavioral responses to stress and preventing stress-induced relapse to alcohol and opioid seeking in rats (Stopponi et al, 2011;Domi et al, 2016;de Guglielmo et al, 2017). Pioglitazone was also shown to reduce heroin craving and anxiety in humans (Jones et al, 2018), and most important, a recent clinical study reported that pioglitazone attenuates measures of nicotine craving (Jones et al, 2017).…”
Section: Significance Statementmentioning
confidence: 99%
“…The stages of drug dependence, oversimplified as abuse/binge-highwithdrawal/compulsion for reuse-relapse (see [90] and [91]), suggest multiple therapeutical timepoints for successful treatment. The PPAR signaling cascade and their metabolic machinery are being considered as an innovative target, among others, for preclinical investigations into the development of therapies against alcohol [92][93][94][95][96][97], tobacco [98][99][100][101][102][103][104][105][106], opioid [107][108][109], and psychostimulant [110,111] dependence. Hence, the repurposing of PPAR-based medications is of increasing interest in this area of neuropsychiatry [111][112][113], although controversial results in humans [114,115] suggest that cautiousness is required.…”
Section: Ppar Agonists In Psychiatric Disordersmentioning
confidence: 99%
“…Three placebo-controlled studies have examined the potential for PPAR-γ agonists in modulating opioid-related outcomes [46][47][48]. In a sample of healthy, non-medical users of prescription opioids, there was no effect of 15 or 45 mg oral pioglitazone administered daily for 2-3 weeks on self-reported positive and negative subjective effects of oxycodone in a single-blind, within-subjects design [46].…”
Section: Ppar-γ Agonistsmentioning
confidence: 99%
“…In addition, pioglitazone had no impact on self-reported drug wanting (opioids, alcohol, cannabis, and tobacco) during the maintenance phases [46]. In a follow-up study, Jones and colleagues assessed the effects of 45 mg oral pioglitazone administered daily for 3 weeks in a sample of non-treatment-seeking adults with an opioid use disorder using a single-blind, randomized, between-subjects design [47]. Pioglitazone did not alter the reinforcing effects of heroin, its abuse liability, or cue reactivity, though self-reported ratings of "I want heroin" were significantly reduced [47].…”
Section: Ppar-γ Agonistsmentioning
confidence: 99%